The Black Heralds: A contradictory contemporaneity - Santiváñez, Roger (2020)
This article will study —in the centenary of César Vallejo’s first book— the return to the lost time of childhood —the maternal home— and the Andean world, exploring the exclusion of the poetic subject in relation to these two fields. It will reveal as a condition of the modern poet, insofar as the verbal reconstruction of the Andean culture, but also the literary, urban and coastal Bohemia (and within its amorous relations) will be submitted by Vallejo to a textual criticism due to its static dimension. The article will explore the various resources —whether symbolist/ modernist, mythological, biblical or indigenist— through which our supreme poet sought to juxtapose that kind of collision aesthetic that shapes the characteristic and proper language of this great poetry.